2018
DOI: 10.3389/fpsyg.2018.01465
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Transcranial Direct Current Stimulation (tDCS) Depending on Previous Musical Training

Abstract: Previous studies have shown that transcranial direct current stimulation (tDCS) facilitates motor performance, but individual differences such as baseline performance seem to influence this effect. Accordingly, musicians offer an inter-individual differences model due to anatomical and functional variances displayed among the motor cortex regions. The aim of the present work was to study if the baseline motor skill predicts whether tDCS can enhance motor learning. For that objective, we administered anodal (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…In a recent meta-analysis, tDCS was found to improve reaction time, execution time and force of contraction during upper limb motor performance. 41 In the wider community, tDCS has been investigated for its potential to enhance performance in fields such as sports 42 and music 43 , and mitigate the detrimental effects of sustained attention on performance by modulating prefrontal activity and increasing the availability of attentional resources. 44 Biofeedback is the process of measuring surrogate markers of arousal (e.g.…”
Section: Future Directions and Stress Amelioration Strategiesmentioning
confidence: 99%
“…In a recent meta-analysis, tDCS was found to improve reaction time, execution time and force of contraction during upper limb motor performance. 41 In the wider community, tDCS has been investigated for its potential to enhance performance in fields such as sports 42 and music 43 , and mitigate the detrimental effects of sustained attention on performance by modulating prefrontal activity and increasing the availability of attentional resources. 44 Biofeedback is the process of measuring surrogate markers of arousal (e.g.…”
Section: Future Directions and Stress Amelioration Strategiesmentioning
confidence: 99%
“…During sleep anodal slow oscillatory transcranial direct current stimulation (so-tDCS; oscillating at ~0.75 Hz) targets the ongoing SO and associated thalamo-cortical network activity [ 50 , 51 ], enhancing SO, spindle activity and improving declarative memory consolidation [ 52–54 ]. Yet, many results with noninvasive brain stimulation results revealed poor reproducibility [ 55–58 ], possibly attributed to pronounced variations in individual network susceptibility and/or electric field distribution [ 59–62 ]. In a previous study of ours, differential effects on sleep associated memory retention of weak exogenous electric stimulation (so-tDCS) correlated with subjects’ memory quotient, an index that indicates one´s memory capacity [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…And the mechanism may be related to the increase of monoamine neurotransmitters in related brain regions. Other studies [ 41 ] have shown that tDCS can also decrease the activity of GABA, increase the level of intracellular Ca 2+ and change the level of brain-derived neurotrophic factor (BDNF). This may be one of the ways tDCS works in PSF.…”
Section: Discussionmentioning
confidence: 99%